Health Literacy: An Effective Component to Overcome Perceived Barriers to Adoption of Preventive Behaviors in the Health Belief Model - Rahman Panahi; Gholamreza Ebrahimi; Seyede Somayeh Kazemi; Mahmoud Tavousi (Hamadan University of Medical Sciences, 2018)
Dear Editor-in-Chief: Health Belief Model is one of the most widely used models in health behaviors and it is considered an individual model of behavioral study. This model measures the relationship between health belief and health behavior, and it is based on the hypothesis that the adoption of preventive behavior is based on the beliefs of the person. In this model, whatever perceived susceptibility, perceived severity, and perceived benefits are stronger, perceived barriers are weaker, and the probability of adoption of preventive health behaviors is greater. In this model, perceived barriers are considered the most important predictors of behavior.